2013
DOI: 10.1002/bem.21825
|View full text |Cite
|
Sign up to set email alerts
|

Simulation study of delivery of subnanosecond pulses to biological tissues with an impulse radiating antenna

Abstract: We have numerically studied the delivery of subnanosecond pulsed radiation to biological tissues for bioelectric applications. The antenna fed by 200 ps pulses uses an elliptical reflector in conjunction with a dielectric lens. Two numerical targets were studied: one was a hemispherical tissue with a resistivity of 0.3-1 S/m and a relative permittivity of 9-70 and the other was a realistic human head model (HUGO). The electromagnetic simulation shows that despite tissue heterogeneity of the human head, the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Thus, psPEFs were considered to have less impact on or result in less damage to surrounding biological tissue, which is of great importance to clinical application, especially in DBS. In addition, studies have shown that a psPEF has great performance in spatial orientation and can achieve electrical focus in breast tissue and even the brain [Guo et al, 2014] by matching impulse‐radiated antennas. Despite our study exploring how psPEFs regulated spike firing in an invasive method, our results showed that psPEF is promising to realize neuromodulation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, psPEFs were considered to have less impact on or result in less damage to surrounding biological tissue, which is of great importance to clinical application, especially in DBS. In addition, studies have shown that a psPEF has great performance in spatial orientation and can achieve electrical focus in breast tissue and even the brain [Guo et al, 2014] by matching impulse‐radiated antennas. Despite our study exploring how psPEFs regulated spike firing in an invasive method, our results showed that psPEF is promising to realize neuromodulation.…”
Section: Discussionmentioning
confidence: 99%
“…Except recently reported studies indicating the possibility of performing electroporation by magnetic fields [39,40] and radiated electromagnetic waves [41], the electric field required for electroporation is delivered by applying high voltages or currents across electrodes within or in contact with the tissue.…”
Section: How Can We Create Electric Fields For Electroporation?mentioning
confidence: 99%
“…More recently, at the same research center, a dielectric rod antenna was also suggested as a candidate for generating subnanosecond PEFs for the stimulation of neurological tissue [16]. All the three techniques have been theoretically investigated using CST software [15], [16], [17], with detailed numerical studies being reported. In contrast, very limited experimental work has been published, and only using rather low voltage subnanosecond pulsed power generators, with the resulting PEFs having extremely low peak values when compared with the values required for electroporation [18], [19], [20], the latter work representing an effort made at University of Limoges (France).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, very limited experimental work has been published, and only using rather low voltage subnanosecond pulsed power generators, with the resulting PEFs having extremely low peak values when compared with the values required for electroporation [18], [19], [20], the latter work representing an effort made at University of Limoges (France). For stimulating deep inside a tissue, say at 8 cm [17] using intense PEFs of some tens of kV/cm, published work suggest a subnanosecond pulsed power generator with a peak output voltage in excess of 250 kV is required [17]. Such a generator is technically extremely challenging.…”
Section: Introductionmentioning
confidence: 99%